High Salt Inhibits Tumor Growth by Enhancing Anti-tumor Immunity - Willebrand, Ralf; Hamad, Ibrahim; Van Zeebroeck, Lauren; Kiss, Máté; Bruderek, Kirsten; Geuzens, Anneleen; Swinnen, Dries; Côrte-Real, Beatriz Fernandes; Markó, Lajos; Lebegge, Els; Laoui, Damya; Kemna, Josephine; et al. (Frontiers in Immunology, 2019)
Excess salt intake could affect the immune system by shifting the immune cell balance towards a pro-inflammatory state. Since this shift of the immune balance is thought to be beneficial in anti-cancer immunity, we tested the impact of high salt diets on tumor growth in mice. Here we show that high salt significantly inhibited tumor growth in two independent murine tumor transplantation models. Although high salt fed tumor-bearing mice showed alterations in T cell populations, the effect seemed to be largely independent of adaptive immune cells. In contrast, depletion of myeloid-derived suppressor cells (MDSCs) significantly reverted the inhibitory effect on tumor growth. In line with this, high salt conditions almost completely blocked murine MDSC function in vitro. Importantly, similar effects were observed in human MDSCs isolated from cancer patients. Thus, high salt conditions seem to inhibit tumor growth by enabling more pronounced anti-tumor immunity through the functional modulation of MDSCs. Our findings might have critical relevance for cancer immunotherapy.